PENGALAMAN PASIEN KANKER PAYUDARA PADA SUKU BATAK YANG MENJALANI KEMOTERAPI - Conny Melva Sianipar; Nurmaini Nurmaini; Nur Afi Darti (Elisabeth Health Jurnal, 2016)
Breast cancer is cancer that comes from the gland, the gland duct and supporting tissue of the breast. One of types of medication for breast cancer is by chemotherapy. Most of the breast cancer patients in North Sumatera are Bataknese women. Goal: The objective of this research was to explore the experience of Bataknese breast cancer patients who were under chemotherapy treatment. Method: The research used phenomenology descriptive method. The data were gathered by conducting in-depth interviews. The sample were 15 Bataknese breast cancer patients who had fulfilled the criteria as the participants, taken by using purposive sampling technique. The Results of recorded interviews was analyzed by using content analysis. Result: The result of the research showed that there were five themes which reflected the phenomena. They were experienced the emotional instability of breast cancer patients as a response to chemotherapy, adaptation to reduce the physical changes after chemotherapy, seeked the healing and recovery by breast cancer patients who were under chemotherapy treatment, reduced the emotional instability by breast cancer patienst who were under chemotherapy treatment, obstacles which is experienced by the breast cancer patients under chemotherapy treatment. It is recommended that health care provider, especially nurse, provide holistic service based on cultural for breast cancer patients who were treated with chemotherapy and give information to educational that the importance of cultural to give the nursing services.